A prediction model for frequency spectrum of blast‐induced seismic wave in viscoelastic medium. (22nd December 2017) - Yu, Chenglong; Wang, Zhongqi; Han, Wengong
ABSTRACT: A prediction model for frequency spectrum of blast‐induced seismic waves is established. The effect of explosive sources is considered in this model. Our model implies that the frequency spectrum of blast‐induced seismic wave is mainly influenced by the initial pressure and the adiabatic exponent of explosives. The dominant frequency increases with the decreasing of initial pressure or the increasing of adiabatic exponent. In addition, this prediction model is verified by the experiment. The error of the dominant frequency is 4%–6%. It is indicated that the proposed model in this paper can reasonably predict the frequency spectrum of blast‐induced seismic waves, and then, we can provide a better frequency spectrum by optimizing the explosion source.